2017
DOI: 10.3946/kjme.2017.69
|View full text |Cite
|
Sign up to set email alerts
|

Podcasting in medical education: a review of the literature

Abstract: Podcasts are increasingly being used for medical education, both within teaching institutions and on an international scale by major journals. To date, there are no evidence-based guidelines for the development of educational podcasts. To review the state of the literature, MEDLINE, SCOPUS, and ERIC were searched in May 2016 for articles describing audio format podcasts used in medical education. Eighty-four articles met inclusion criteria. A qualitative synthesis of the evidence was done using Kirkpatrick’s m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
133
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(145 citation statements)
references
References 38 publications
5
133
0
7
Order By: Relevance
“…Initially, this included mostly dissemination via blogs, wikis, and podcasts, but more recently has evolved to include other media, such as microblogging (e.g., Twitter), social networks (e.g., Facebook, LinkedIn), and video-based outlets (e.g., YouTube). Increasingly, academic journals are leveraging social media to encourage readers to engage with their materials [14] and are experimenting with using online social media conversations [15,16], infographics [17,18] and podcasts [17,19,20] to increase readers' awareness of new publications. In many ways, knowledge translation is a scientist-based description of a phenomenon that overlaps with the individual end-user's education, especially when they intersect within social media platforms.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, this included mostly dissemination via blogs, wikis, and podcasts, but more recently has evolved to include other media, such as microblogging (e.g., Twitter), social networks (e.g., Facebook, LinkedIn), and video-based outlets (e.g., YouTube). Increasingly, academic journals are leveraging social media to encourage readers to engage with their materials [14] and are experimenting with using online social media conversations [15,16], infographics [17,18] and podcasts [17,19,20] to increase readers' awareness of new publications. In many ways, knowledge translation is a scientist-based description of a phenomenon that overlaps with the individual end-user's education, especially when they intersect within social media platforms.…”
Section: Introductionmentioning
confidence: 99%
“…The use of podcasts to educate and inform physicians has been rapidly expanding; most recently graduated physicians and those still in training are increasingly exposed to podcasts during their formal and continuing education [1,[8][9][10]. While it has been shown that medical podcasts, in general, have increased in number and popularity over the past 20 years, a recent study had cataloged current medical podcasts and determined EM had the largest number of podcasts and the most available content [2,7].…”
Section: Discussionmentioning
confidence: 99%
“…EMS was found to have more active and inactive podcasts, but Medical Education was found to have a much higher amount of content, with 1.5-times the number of available episodes as EMS and 4-6-times the number of episodes as Ultrasound and Toxicology (the next two most active subspecialties). Other EM subspecialties had limited content available, which provides a gateway for members of these subspecialties to publish additional educational opportunities in what many learners have found to be a favorable means of obtaining medical content and potentially continuing medical education credit [1,2,[7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Over two-thirds (74) said they would like their publication promoted on social media, ResearchGate (70) being the most preferred platform, followed by Twitter (40), Facebook (37), WhatsApp (35), Academia.edu (27), and LinkedIn (26). Only five said they would not prefer their publication being promoted.…”
Section: Social Media Promotions and Platformsmentioning
confidence: 99%